The effect of human resources, internal control system, and implementation effectiveness of village financial systems on village financial statements quality (Survey on entire village in Bantul district) - Jatmiko, Bambang; Prawoto, Nano; Astuti, Rini Juni; Wulandari, Desy (MEC-J (Management and Economics Journal), 2019)
The research objectives are follows: (1) to test and prove empirically the effect of human resources on village Financial Reports Quality; (2) to test and prove empirically the effect of internal controls on village Financial Reports Quality. (3) to test and prove empirically the effectiveness of Village Financial System (SISKEUDES) on the village Financial Reports Quality. The research object were villages in Bantul Regency. The samples were 43 villages selected by purposive sampling method. The respondent targets were village heads, village secretaries, or financial staff. This study uses a quantitative method with primary data collection by questionnaires. The study results show that human resources in villages of Bantul Regency are still low due to lack of training and experience to make financial reports. The internal control system of villages in Bantul Regency is quite satisfactory. They have understood the procedures of their respective main tasks and functions, the risks faced of their mistakes and frauds. The Village Financial System in villages of Bantul Regency has been effectively implemented because all villages have used the Village Financial System application in order all the financial reports can be directly accounted for by central government.